2013
DOI: 10.1103/physreve.88.062919
|View full text |Cite
|
Sign up to set email alerts
|

Universal asymptotic behavior in nonlinear systems driven by a two-frequency forcing

Abstract: We examine the time-dependent behavior of a nonlinear system driven by a two-frequency forcing. By using a nonperturbative approach, we are able to derive an asymptotic expression, valid in the long-time limit, for the time average of the output variable which describes the response of the system. We identify several universal features of the asymptotic response of the system, which are independent of the details of the model. In particular, we determine an asymptotic expression for the width of the resonance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Using equation (8), it can easily be seen that the stationary value Q st t (Ω 0 , ϕ) is a T -periodic function of time. A further interesting fact is that the infinite-time average Q ∞ (Ω 0 , ϕ) displays a higher symmetry in ϕ than the obvious ϕ 1 → ϕ 1 + 2π and ϕ 2 → ϕ 2 + 2π [14]. To see that this is so, note that in the present case the condition k • Ω 0 = 0 becomes equivalent to k 1 q + k 2 p = 0.…”
Section: Commensurable Frequencies and Periodicity In ϕmentioning
confidence: 68%
See 1 more Smart Citation
“…Using equation (8), it can easily be seen that the stationary value Q st t (Ω 0 , ϕ) is a T -periodic function of time. A further interesting fact is that the infinite-time average Q ∞ (Ω 0 , ϕ) displays a higher symmetry in ϕ than the obvious ϕ 1 → ϕ 1 + 2π and ϕ 2 → ϕ 2 + 2π [14]. To see that this is so, note that in the present case the condition k • Ω 0 = 0 becomes equivalent to k 1 q + k 2 p = 0.…”
Section: Commensurable Frequencies and Periodicity In ϕmentioning
confidence: 68%
“…The common physics behind these phenomena is an interplay of non-linearities and non-equilibrium. Driven systems have been studied in the Hamiltonian limit [11][12][13], as well as in the steady state of dissipative classical [8,9,14,15] and quantum mechanical models [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It was in particular shown that for the kicked rotor system quantum interference leads to a sub-Fourier response [1][2][3]. Sub-Fourier behaviour was also observed in bi-harmonically driven classical systems [4]. In both cases, the underlying mechanism relies on the system's extreme sensitivity to the nature of the driving, with periodic and quasiperiodic drivings leading to a completely different response.…”
mentioning
confidence: 95%
“…In Sec. III we revisit the * dcubero@us.es † f.renzoni@ucl.ac.uk asymptotic theory for classical systems [9,10] which will be useful as an introduction to the quantum case, fully discussed in Sec. IV.…”
Section: Introductionmentioning
confidence: 99%